2000
DOI: 10.1097/00003072-200007000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Imaging With Pertechnetate Plus Perchlorate/MIBI Subtraction Scintigraphy

Abstract: We set up a modified technetium-99m (Tc-99m) pertechnetate/Tc-99m MIBI (Tc-MIBI) subtraction scintigraphy for parathyroid imaging by introducing the use of potassium perchlorate (KCLO4). Initially, the effect of KCLO4 on technetium thyroid wash-out was evaluated in five healthy volunteers: 40-minute dynamic studies of the thyroid were obtained 20 minutes after the injection of technetium 150 MBq (4 mCi), both in baseline conditions and after the oral administration of 400 mg KCLO4. After an average latency tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…18 However, other investigators have reported that this issue can be solved by combining MIBI scintigraphy with 123 I or 99m Tc-pertechnetate, which is a specific tracer for the thyroid node. 19,20 In our study, no falsepositive results due to nodular lesion of the thyroid gland were obtained when combining MIBI scintigraphy with neck US.…”
Section: Discussionmentioning
confidence: 49%
“…18 However, other investigators have reported that this issue can be solved by combining MIBI scintigraphy with 123 I or 99m Tc-pertechnetate, which is a specific tracer for the thyroid node. 19,20 In our study, no falsepositive results due to nodular lesion of the thyroid gland were obtained when combining MIBI scintigraphy with neck US.…”
Section: Discussionmentioning
confidence: 49%
“…For this reason the double-tracer scan is usually preferred in geographic areas with a high prevalence of nodular goiter (21,23). We utilize a double-tracer subtraction scintigraphy using 99m Tc-pertechnetate as a thyroid agent, which is significantly cheaper than 123 I (14). Moreover, a correlative ultrasound imaging is useful to differentiate thyroid from parathyroid enlargements (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative localizing imaging work-up consisted of a double-tracer 99m Tc-pertechnetate/MIBI subtraction scan combined with high-resolution neck ultrasound (14). In cases of congruent scan/ultrasound results (both positive or negative) imaging was terminated, while in some cases of discrepancy (scan-positive and ultrasound-negative) for the presence of an enlarged parathyroid gland in the neck or with planar scintigraphy showing an ectopic parathyroid gland, the imaging protocol was completed by tomographic (single photon emission computed tomography (SPECT)) acquisition (n ¼ 36 patients) in order to better define the depth of the parathyroid enlargement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the relatively low sensitivity of preoperative imaging observed by Bonjer et al [20] might have been related, at least in part, to the method used for scintigraphic acquisition, namely a dual-phase planar technique. A number of recent studies have demonstrated that the sensitivity of 99m Tc-MIBI scintigraphy in detecting parathyroid adenomas is 90% or higher when a dual-tracer technique or a dual-phase SPET technique is employed [17,21,22,23].…”
mentioning
confidence: 99%